Implementation of Cyber Counseling to Improve the Accessibility of Counseling Services (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
In today's digital age, the need for easily accessible counseling services is increasingly urgent, especially among individuals with geographic or mobility limitations. This research aims to explore the implementation of cyber counseling as a solution to improve the accessibility of counseling services. This research identifies the challenges faced in implementing cyber counseling, including data privacy and security issues, as well as the need for training for counselors to use technology effectively. The method used was a literature review, by analyzing various academic sources, relevant articles and reports regarding cyber counseling and its impact on the accessibility of mental health services. The main source of research data is scientific articles on the database on google scholar. with a publication range of 1988 to 2024. The keywords used in the journal search were "cyber counseling services", "global cyber counseling era", and "cyber counseling in schools". Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawn. The results of the analysis show that cyber counseling has great potential to improve the accessibility of counseling services, but there needs to be more attention to the technical and ethical aspects of its implementation